Holism and qualitative research within the framework of the anthropology of complexity. A reflection on the methodological pertinence in socio-sanitary and human sciences - José Siles González; María del Carmen Solano Ruiz; Luis Cibanal Juan (Universidad de Alicante, 2012)
This study was organised around the following objectives: Relating the principle of methodological and instrumental pertinence to the characteristics of the object-subject on which research is done within the epistemological framework of a discipline, and Reflecting on the pertinence of qualitative research and historico-ethnographic sources in socio-sanitary sciences (particularly nursing) and human sciences (due to their holism) The theme development was structured through a process of analysis that focused on the three crucial phases in Edgar Morin's work: the Dialectics between the real and the imaginary (anthropology of death); the anthropocosmological dialectics, and finally, the anthropo-bio-cosmic dialogics. Conclusions: From Morin on, the vision of reality became more multidimensional and holistic, since until well into the 20th century, knowledge had been based on abstraction, subdivision, simplification, reductionism, law generation, etc. Morin wanted to humanise science through a transdisciplinary anthropology in which the experiential dynamics of the human being was considered in a more global way starting from the paradigm of complexity, the qualitative methodology being a pertinent instrument for holistic clarification.